2011
DOI: 10.3109/10428194.2011.578310
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of chronic myeloid leukemia imatinib-resistant patients: do BCR–ABL kinase domain mutations affect patient survival? First multicenter Argentinean study

Abstract: In imatinib-treated patients with chronic myeloid leukemia (CML), BCR-ABL mutations are the most common mechanism of resistance. Here we report the first multicenter Argentinean study investigating mutations in those patients with CML who fail or lose response to imatinib, with or without previous interferon treatment. Point mutations were detected in 36 of 154 patients by direct sequencing. In our series, the single most common mutations were G250E, E255K/V, and M351T. The presence of mutations correlated sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Although in some studies survival was usually calculated from the start of IM therapy (11)(12)(13)(14)(15), we calculated survival from the time of mutation assessment, similar to a previous report (13). This choice relied on the greater accuracy of data, considering that this is a retrospective, multicenter study from several Latin American countries and criteria could not be homogeneous.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although in some studies survival was usually calculated from the start of IM therapy (11)(12)(13)(14)(15), we calculated survival from the time of mutation assessment, similar to a previous report (13). This choice relied on the greater accuracy of data, considering that this is a retrospective, multicenter study from several Latin American countries and criteria could not be homogeneous.…”
Section: Discussionmentioning
confidence: 98%
“…Five participating institutions (University of São Paulo-Brazil; Instituto de Investigaciones Hematológicas, Academia Nacional de Medicina-Argentina; University of Campinas (Unicamp)-Brazil; Federal University of Paraná-Brazil; and Instituto Nacional do Câncer-Brazil), performed all of the analysis, following previously described methods (11,15). Briefly, total RNA were transcribed to cDNA and then amplified with Taq platinum high fidelity and primers, which annealed forward to BCR exon b2 and reverse to ABL exon 10.…”
Section: Bcr-abl Mutation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Even though TKI therapy has revolutionized the treatment of CML, its availability in underdeveloped and developing countries, such as Argentina, Brazil or Bosnia has been limited, as well as in some developed countries because of financial considerations and lack of insurance cover (Bengio et al , ). The importance of studying delayed TKI therapy in patients transcends the local and individual level and extrapolates to a more global health care issue, because many developing countries have gradually introduced TKI therapy and still have patients who wait for TKI therapy.…”
mentioning
confidence: 99%
“…For the former, the most effective method is RNA interference (Zaree-Mahmodabady et al, 2010), and the specific inhibitor STI571 is used in the case of the latter. Previous studies have shown that RNA interference and STI571 alone have some limitations, such as transfection efficiency, toxicity and drug resistance (Swords et al, 2009;Bengió et al, 2011), especially in the acute transformation phase of CML with more abnormal genes (Yamauchi and Ueda, 2011;Nicolini et al, 2011). In the acute transformation phase, combined treatment is the trend for CML (Druker et al, 2002).…”
Section: Introductionmentioning
confidence: 99%